A report of the major farm practice in Virginia Farms Compostela, Cebu - Kempis, Evelina; Alonzo, Jenny Lind; De Mayo, Angeles; Umacob, Carolina
This study describes the observed operations management of Virginia Farm 2 in Cebu.